Rise of social network based seafood industrial cluster and rural community transformation in Zhoushan Islands of China - Xu, Yue, author; Raynolds, Laura T., advisor; Mao, KuoRay, committee member; Kwiatkowski, Lynn, committee member (Colorado State University. Libraries, 2021)
This thesis reviews the historical, political, and cultural foundations for establishing seafood industrial clusters at Zhoushan Islands, explaining the organizational level management, operation, and regulatory strategies utilized by seafood factory owners to achieve their success. This thesis explores the general labor pattern, the surveillance and hierarchies in seafood factories at Zhoushan Islands, inequalities and social stratification in the nearby local rural community, and the invisible consequences of state-led industrialization and rural transformation policies in the Zhoushan industrial cluster. A theme running through this discussion is how factory owners utilize available political, social, and economic capital from the elite social networks to build their pathway to succeed in operating seafood business, countering barriers, and handling potential risks.
Keywords: East Asia; rural transformation; social network; industrial cluster; development studies; seafood processing